The Early Maternal Skin-to-Skin Contact and Its Role in Reducing Neonatal Sepsis: A Prospective Cohort Study - Farooqui, Shaista; S Karim, Mehtab; Rizvi, Sameera Ali; Ali, Syeda Tabeena (ADVANCES IN BASIC MEDICAL SCIENCES, 2025)
OBJECTIVE: To assess the impact of maternal-newborn skin-to-skin contact on the incidence of neonatal sepsis by the 28th day of life among mothers delivering at hospitals in Baluchistan and Karachi. METHODOLOGY: This prospective cohort study was conducted from December to April 2022, including 237 mothers and their neonates from two sites: Civil Hospital Hub, Lasbela District, Baluchistan (SSC/KMC group) and Civil Hospital Karachi (conventional care group). Participants were selected using purposive sampling. Data collected through a structured, pretested questionnaire and by observation from delivery until the 28th day of life to determine the occurrence of neonatal sepsis in both groups. Data were entered into SPSS version 22 and analyzed using binary logistic regression. Variables showing a p-value less than 0.25 in the bivariate analysis were entered into the multivariate logistic regression model to account for potential confounding factors. Statistical significance in the multivariate model was determined at a p-value threshold of <0.05. RESULTS: Among the 237 neonates, 18.5% developed early-onset sepsis (0–7 days), and 4.2% developed late-onset sepsis (8–28 days), yielding an overall sepsis rate of 22.6%. Significant associations were found between neonatal sepsis and factors such as maternal age, ethnicity, low birth weight, lack of SSC, and delayed initiation of breastfeeding. Attributable risk analysis revealed that 18.76% of sepsis cases in the non-SSC group could have been prevented by early skin-to-skin contact (SSC). Furthermore, 58.26% of the sepsis burden in neonates without SSC was potentially preventable through timely SSC intervention. CONCLUSION: Early SSC and breastfeeding initiation are simple, cost-effective interventions that significantly reduce neonatal sepsis, morbidity, and mortality. Promoting antenatal and postnatal care awareness, ensuring skilled birth attendance, and adhering to infection prevention protocols are critical steps towards improving neonatal outcomes.